Systematic Review of the Common Pathophysiological Mechanisms in COVID-19 and Neurodegeneration: The Role of Bioactive Compounds and Natural Antioxidants - Kyonghwan Choe; Hyun Young Park; Muhammad Ikram; Hyeon Jin Lee; Tae Ju Park; Rahat Ullah; Myeong Ok Kim (Cells, 2022)
The novel coronavirus (2019-nCoVCOVID-19) belongs to the Beta coronavirus family, which contains MERS-CoV (Middle East respiratory syndrome coronavirus) and SARS-CoV (severe acute respiratory syndrome coronavirus). SARS-CoV-2 activates the innate immune system, thereby activating the inflammatory mechanism, causing the release of inflammatory cytokines. Moreover, it has been suggested that COVID-19 may penetrate the central nervous system, and release inflammatory cytokines in the brains, inducing neuroinflammation and neurodegeneration. Several links connect COVID-19 with Alzheimer’s disease (AD), such as elevated oxidative stress, uncontrolled release of the inflammatory cytokines, and mitochondrial apoptosis. There are severe concerns that excessive immune cell activation in COVID-19 may aggravate the neurodegeneration and amyloid-beta pathology of AD. Here, we have collected the evidence, showing the links between the two diseases. The focus has been made to collect the information on the activation of the inflammation, its contributors, and shared therapeutic targets. Furthermore, we have given future perspectives, research gaps, and overlapping pathological bases of the two diseases. Lastly, we have given the short touch to the drugs that have equally shown rescuing effects against both diseases. Although there is limited information available regarding the exact links between COVID-19 and neuroinflammation, we have insight into the pathological contributors of the diseases. Based on the shared pathological features and therapeutic targets, we hypothesize that the activation of the immune system may induce neurological disorders by triggering oxidative stress and neuroinflammation.